CYBERSECURITY FRAMEWORK FOR AUTONOMOUS ENGINEERING SYSTEMS IN INDUSTRY 5.0 - Syawal Aprian; Adhe Ronny Julians; Nursahar Buang (INJOSEDU: International Journal of Social and Education, 2026)
The rapid adoption of autonomous engineering systems in the Industry 5.0 era has transformed industrial operations through the integration of artificial intelligence, the Internet of Things, cyber-physical systems, and advanced automation technologies. While these innovations enhance productivity, flexibility, and human–machine collaboration, they also introduce complex cybersecurity challenges that threaten system reliability, data integrity, operational continuity, and organizational resilience. This study aims to examine the development of cybersecurity frameworks for autonomous engineering systems within the context of Industry 5.0 through a literature review approach. The research method employs a systematic examination of scholarly articles, conference proceedings, industry reports, and relevant policy documents related to cybersecurity, autonomous systems, and Industry 5.0. The findings indicate that effective cybersecurity frameworks require a multidimensional approach encompassing risk assessment, zero-trust architecture, artificial intelligence-driven threat detection, secure communication protocols, continuous monitoring, and human-centered security governance. Furthermore, the integration of cybersecurity-by-design principles throughout the system lifecycle is essential for minimizing vulnerabilities and improving resilience against evolving cyber threats. The study concludes that a comprehensive cybersecurity framework is a critical prerequisite for ensuring the secure, reliable, and sustainable deployment of autonomous engineering systems in Industry 5.0 environments. The results contribute to the development of strategic guidelines for organizations, engineers, and policymakers seeking to strengthen cybersecurity readiness in increasingly autonomous industrial ecosystems.